Understanding the patient and supporter journey in cocaine use disorder - Leclair, Denise; Waye, Katherine M.; Gomez-Mancilla, Baltazar; Kiluk, Brian D.; Karanam, Ananda Krishna; Banerjee, Partha S.; Muthusamy, Velusamy Shanmuganathan; Maahs, Suzanne (Frontiers in Psychiatry, 2024)
Background There is a paucity of literature describing experiences and journey of individuals with cocaine use disorder (CUD) and supporters who care for them. The aim of this study was to understand and document the journey of individuals with current CUD, those in CUD remission, and supporters. Methods The online bulletin board (OBB) is a qualitative tool where participants engage in an interactive discussion on a virtual forum. After completing a 15-minute screening questionnaire determining eligibility, individuals in CUD remission and supporters participated in an OBB for 60 minutes, split across 8 days over 2 weeks. Individuals with current CUD participated in a one-time virtual focus group discussion for 90 minutes. Results Individuals in CUD remission (n=35) were from Brazil, France, Spain, the UK, and the US; those with current CUD (n=5) and supporters (n=6) were from the US. Key insights were that individuals with current CUD were seeking a ‘euphoric high’ that cocaine provides. Those in CUD remission described a ‘euphoric high’ when they first tried cocaine, but over time it became harder to re-create this feeling. Individuals in CUD remission expressed a ‘rollercoaster’ of emotions from when they first started using cocaine to when they stopped. Supporters were sad, isolated, and worried about a potential cocaine overdose for their loved ones with CUD. Conclusion The study provides valuable insights into the experiences and journey of individuals with CUD and their supporters. Data generated from this study gives insights into this under-served and growing population.